A Study on the use of computer mediated communication for the relational maintenance of female domestic helpers with their children in the province - Carnecer, Cecilia Maris S.; Jamandre, Neil Kenneth F. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2019)
Female household domestic helpers and their children are faced with the difficulty of maintaining relationships with each other because of the physical distance between them and limited intimacy that they can show to one another due to the limitations of available technologies that can channel communication. This study focused on the narratives of female household domestic helpers and their children and the relationship maintenance strategies that they use. The research objectives were to identify the means, frequency, and duration of communication, examine the relationship maintenance strategies used, and to identify the challenges in the communication, between the female household domestic helpers and their children. A qualitative research design was used to fulfill the objectives of this study, which utilized face-to-face and telephone interviews as its method of inquiry. The participants of the interviews were female household domestic helpers working in Metro Manila. Three female household domestic helpers were interviewed and three of their children were interviewed. The data was analyzed using thematic analysis, also using the Relational Dialectics Theory by Baxter & Montgomery and the Social Presence Theory by Short, Williams and Christie (1976) as cited in Gunawardena (1995). The results show that calling with the use of a cellphone has been effective in maintaining relationships between the female household domestic helpers and their children despite the distance between them.
Thesis (B.A. in Speech Communication)--University of the Philippines Diliman
Includes bibliographical references and appendices.